Application of microcontroller to control pneumatic actuator - Mohammad Safuan, Sheafi (2010)
Pneumatics Technology is capable of utilizing the compressed air to perform work and to organize functions. Pneumatic actuator, which is one of the elements in pneumatic system, has been recognized for its flexibility to do various types of work and its capability in diversity of applications. Commonly known controller to control the pneumatic system movements is Programmable Logic Controller (PLC). However, the cost of PLC is expensive for small automation system and it size basis can be consider large as a controller. To overcome this problem, there is a new thought to use Programmable Interface Controller (PIC) which is smaller and cheaper to replace PLC. Main purpose of this project is to make the idea alive. This project will mainly concerned on controlling the sequence of the three linear double-acting cylinder actuator movements by using microcontroller PIC 18F452 coupled with pneumatic solenoid valve. This microcontroller is used for controlling predefined sequences of opening and closing of solenoid valves that will activate the actuator. A program in MikroC PRO is written and developed to communicate with the microcontroller as to move the actuator according to plan sequences. For purpose of voltage regulation, a single-pole double throw (SPDT) relays are used as “OUTPUT” signal from the sensor for the microcontroller. The “OUTPUT RELAY” is of the 6V SPDT powered from the switching output voltage 5V dc of the microcontroller to convey the 24V dc to control the solenoid pneumatic valve. The application that is going to be developed must be in a low cost and a small scale basis. Subsequently, experimental simulation tests will be conducted to evaluate the response and accuracy behaviour of the microcontroller interacting with the solenoid valves.